Inflammatory markers and their association with main cardiovascular risk factors in patients with atrial fibrillation and arterial hypertension - O. A. Tarasova (Российский кардиологический журнал)
According to modern views, immuno-inflammatory activation plays an important role in atrial fibrillation (AF) pathogenesis. In 97patients with arterial hypertension (AH), paroxysm and non-paroxysm levels of C-reactive protein (CRP), tumor necrosis factor-alpha (TNF-alpha), and fibrinogen were measured in 97 patients with permanent, persisting recurrent atrial fibrillation (AF). During AF paroxysm, TNF-alpha levels were significantly increased (p = 0,0001), in contrast with relatively stable CRP and fibrinogen levels (p > 0,05). CRP inversely correlated with AF severity (p = 0,0001). TNF-alpha levels were inversely associated with high-density lipoprotein cholesterol concentration in AF-free hypertensives, AH and permanent AF individuals, and persistent recurrent AF patients during the paroxysm. AF paroxysms were linked to increased TNF-alpha concentration. The correlation between main cardiovascular risk factors and inflammatory markers was observed.